Airway Pressure Release Ventilation With Time-Controlled Adaptive Ventilation (TCAV™) in COVID-19: A Community Hospital’s Experience - Rola, Philippe; Daxon, Benjamin (Frontiers in Physiology, 2022)
Santa Cabrini Ospedale, a community hospital in Montreal, Canada, used the APRV-TCAV™ approach for several patients in the first wave of the COVID-19 outbreak in the spring of 2021. Based on a favorable patient response it became the primary mode of invasive mechanical ventilation from initiation of mechanical ventilation through extubation during the 2nd and 3rd waves of the COVID-19 patients. In this article we describe our success with utilizing Airway Pressure Release Ventilation with a Time-Controlled Adaptive Ventilation protocol (APRV-TCAV™) over more conventional modes and protocols and look at three cases that aptly demonstrate our experience. We then outline several risks with our approach and the lessons learned from our experience. While we generally saw improvement in our patients’ clinical course with APRV-TCAV™ there are inherent risks with this approach that others must prepare for if they attempt to implement it in their practice.